Bleeding due to acquired dysfibrinogenemia as the initial presentation of multiple myeloma. Issue 7 (17th July 2019) - Siddiq, Namrah; Bergstrom, Colin; Anderson, Larry D; Nagalla, Srikanth
Abstract : Patients with multiple myeloma (MM) are at risk for acquired dysfibrinogenemia resulting in laboratory abnormalities and/or bleeding complications. We describe a 63-year-old man who presented with bleeding diathesis in the presence of a low fibrinogen activity level with a normal fibrinogen antigen level. Further studies revealed elevated levels of lambda free light chains, and he was diagnosed with MM. Despite initiating treatment with bortezomib/dexamethasone, he continued to have recurrent bleeds along with hypofibrinogenaemia, prompting a switch to carfilzomib/dexamethasone. The patient responded with improvement in bleeding symptoms, normalisation of fibrinogen activity and a decrease in serum free light chains.